2015
DOI: 10.1111/psyg.12129
|View full text |Cite
|
Sign up to set email alerts
|

Increased medical cost metrics for patients 50 years of age and older in the collaborate care model of treatment for depression

Abstract: Medical cost utilization in the 6 months after diagnosis of depression was significantly higher in patients in the upper age quartile (≥ 50 years) enrolled in CCM than those in the lower quartiles (age < 50).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, minor or sub‐threshold depression, depression and anxiety in residential care homes, suicidal ideation, alcohol abuse, behavioural symptoms in Alzheimer, and mental problems in specific patient groups …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, minor or sub‐threshold depression, depression and anxiety in residential care homes, suicidal ideation, alcohol abuse, behavioural symptoms in Alzheimer, and mental problems in specific patient groups …”
Section: Resultsmentioning
confidence: 99%
“…The implementation strategies mentioned above were used alone or in combination for managing specific MHP in the elderly population such as major depression, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] minor or sub-threshold depression, [39][40][41][42] depression and anxiety in residential care homes, [43][44][45][46][47] suicidal ideation, 48 alcohol abuse, 49,50 behavioural symptoms in Alzheimer, 51 and mental problems in specific patient groups. 15,[52][53][54][55][56] Evidence showed that the collaborative care strategy is best adapted for the organisation of MHCE, often combined with one of the other operational strategies (see Table 1).…”
Section: Operational Strategiesmentioning
confidence: 99%
“…The prevalence of unmet medical needs has been found to be higher among those with worse mobility or with chronic pain due to the resultant difficulties with mobility [43]. Past studies have also found unmet medical needs to be associated with worse self-rated health status [44] and depression [45,46] because of the costs related to depression [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, acceptability-related reasons for unmet medical needs may have a strong in uence on such individuals accessing medical services [21]. Moreover, severe depression may have a signi cant impact on access-related reasons for unmet medical needs, as depression can lead to poor health behavior [60] and nancial burdens [61,62]. Further, we found that obesity causes low access, which we considered to be related to the physical restrictions owing to obesity-associated pain and physical discomfort.…”
Section: Discussionmentioning
confidence: 99%